Analysis of the Extended Hollo-Bolt component in concrete-filled steel connections - Cabrera Duran, Manuela (2023)
Steel Hollow Sections (SHS) offer many structural, economical and architectural advantages. However, their use is limited due to the difficulties of site bolting using standard bolts. Blind-bolted systems overcome this limitation as they only require access to one side of the hollow section to tighten the bolt. They are also an alternative to site welding. Commercially available blind bolts are restricted to be used in simple connections due to their limited contribution to the stiffness.